Cololejeunea microscopica var. microscopica (Marchantiophyta: Lejeuneaceae) – A new record for India (Bangladesh Journal of Plant Taxonomy, 2017)
Not available.Bangladesh J. Plant Taxon. 24(2): 233–236.